Growth performance of nursery pigs fed BIOSAF yeast alone or in combination with in-feed antimicrobial - Hildabrand, B.M.; Neill, C.R.; Burkey, T.E.; Johnson, B.J.; Minton, J. Ernest; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 210 pigs were used in a 28-d growth study to evaluate the effects of feeding the combination antibiotic neomycin and oxytetracycline (Neo-Terra), different rates of BIOSAF yeast (0.15% or 0.3%), and the combination of Neo-Terra and BIOSAF in nursery diets. Overall, pigs fed the diet containing both Neo-Terra and 0.15% BIOSAF had greater ADG and ADFI than did pigs fed the control diet and pigs fed either concentration of BIOSAF alone (P<0.05). Furthermore, over the entire trial, pigs fed the diet containing both Neo-Terra and BIOSAF also tended to have greater ADG and ADFI than did pigs fed only Neo-Terra (P = 0.15). Pigs fed Neo-Terra had greater ADG and ADFI than did pigs fed the control diet and the diet containing 0.15% BIOSAF, but both ADG and ADFI were similar between pigs fed Neo-Terra and pigs fed 0.3% BIOSAF. Whereas BIOSAF fed alone did not significantly improve growth performance over that of control pigs, pigs fed the diet combining both Neo-Terra and 0.15% BIOSAF had a 16% improvement in ADG, compared with that of pigs fed the control diet, and had a trend for an improvement in ADG, compared with that of pigs fed the diet containing Neo-Terra without added yeast. Thus, in nursery settings where Neo-Terra will be added, addition of 0.15% BIOSAF to diets could enhance growth performance. The overall growth performance of pigs fed 0.3% BIOSAF yeast was intermediate to that of pigs fed the control diet and pigs fed the diet containing Neo-Terra. Additional research will be required to determine definitively if a rate at, or close to, 0.3% BIOSAF can be added to nursery diets to approach growth performance observed with Neo-Terra.
Keywords: Antimicrobials; BIOSAF; Neomycin; Oxytetracycline; Nursery pigs; Pigs; Swine